EXPLORING PRODUCT AWARENESS AND PURCHASE INFLUENCES AMONG RURAL CONSUMERS IN WEST BENGAL - Ghosh, Kshanaprava; Pandey, Ravindra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The marketing of FMCG products is heavily dependent on customer behavior. A number of things influence this behavior. The demands and requirements of customers in this age of globalization are ever-evolving. Increases in India's gross domestic product (GDP) is mostly attributable to the fast-moving consumer goods (FMCG) industry. So, it's important to track how people are changing their purchasing habits in relation to fast-moving consumer goods. The purpose of this exploratory research project is to examine the purchasing habits of rural residents of Bankura District, West Bengal, with respect to FMCG. Two hundred and twenty rural customers were chosen using a purposive sample technique. Additionally, the survey shows that among the factors driving customer purchases, quality ranks highest with 26.82% of respondents, followed by price with 20.45% and taste with 17.27%. These results show that when it comes to fast-moving consumer goods (FMCG), quality and price are the two most important factors influencing rural customers' buying decisions.